The Effect of Implementing the Agribusiness System on Increasing the Income of Vegetable Farmers in Kuantan Singingi Regency - Susanto, Haris; Mashadi, Mashadi; Sasmi, Meli; Hariadi, Hariadi; Kusuma, Arya Diki (Baselang, 2023)
This research aims to determine the application of the agribusiness system to vegetable farmers which includes the production facilities sub-system, cultivation sub-system, handling and post-harvest sub-system and product marketing sub-system and to determine the effect of implementing the agribusiness system on the income level of vegetable farmers. The research was conducted using the survey method. A survey is research that takes samples from a population and uses a questionnaire as the main data collection tool. Meanwhile, the sampling method used was Stratified Purposive Sampling. Based on the results of research regarding the influence of the application of the agribusiness subsystem on the income of vegetable farmers, it can be concluded as follows: The application of the vegetable agribusiness system has been implemented well by respondents, especially in the production and marketing facilities subsystem. The independent variables of the production facilities subsystem (X1), farming subsystem (X2), post-harvest handling and processing subsystem (X3) and marketing subsystem (X4) which have a significant effect on income are the production and marketing facilities subsystem, because they have a smaller P-value from real level = α 0.05. Meanwhile, the post-harvest handling and processing subsystem has no real effect on income, because it has a P-value greater than the real level = α 0.05.